PERAMALAN JUMLAH PERMINTAAN AIR MINUM DALAM KEMASAN - , Ihsan Hasan, S.T., Ir. Lukito Edi Nugroho, MSc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Forecasting is very important in production to predict the number of demand in the future. Forecasting helps industrial organization maintaining inventory level and stock out rate. Bottled drinking water is a kind of functional product because it doesnât has a lot of type of product and has long cycle period. Simplest forecasting method such as Moving average and exponential smoothing are fit to be used to forecast the number of demand in the future. Web-base demand forecasting application is easy to be used because user doesnât need to determine the number of moving average and smoothing value. The application shows only the best method which has smallest MAPE value. Historical demand data of bottled drinking water collected since January 2003 until March 2011. Demand for the next 12 months predicted using web-base demand forecasting application, start from April 2010 until March 2011. Demand forecasting of gallon product is 13.688 gallon and the best method to forecast is single exponential smoothing. Demand forecasting of bottle product for April 2010